Louis van Gaal the biography - Meijer, Maarten 1958- (Ebury Press, 2015)
So who is Louis van Gaal? An inflexible ex-PE teacher who only knows how to act like a dictator or a footballing visionary that has made him one of the greatest ever European managers? Wherever he has gone, Van Gaal has been accused of being a domineering disciplinarian and a control freak. He is certainly, by his own admission, a man who leaves nothing to chance. A disciple in the 1970s of Rinus Michels' Total Football philosophy, he is a fascinating contradiction - an ultra-individualist utterly devoted to the collective effort. He believes in the team over the individual, in always having a plan and a team prepared to follow it. Van Gaal led the young Ajax team he moulded to Champions League glory in 1995, went on to win titles across Europe with Barcelona, AZ Alkmaar and Bayern Munich and served two stints as national coach of Holland. It is a career that has never been short on colour and drama - from fallouts with players to rants at the media wherever he has managed. Dutch football commentator Maarten Meijer's has written the definitive biography of van Gaal - both the man and his methods
Keywords: Gaal, Louis van; Gaal, Louis van -- 1951-; Soccer managers / Netherlands / Biography; Trainer; Fußball; Niederlande; Biografie